(untitled) (Asian Education Studies, 2020)
The present study aimed to explore the attitudes of primary school students in Saudi Arabia towards using PowerPoint program in classroom. A descriptive analytical approach was adopted and a questionnaire was developed. The researcher selected a purposive sample consisting of305 sixth grade male students from five primary schools in Al-Sulail, Saudi Arabia. The questionnaire forms were distributed to all of those students. All of the distributed forms were retrieved and considered valid for analysis. SPSS program was used. It was found that most of the primary school students in Saudi Arabia have excellent skills in using the PowerPoint program. It was found that primary school students in Saudi Arabia have positive attitudes towards using PowerPoint program in classroom. It was found that using PowerPoint enriches students’ knowledge, and increases their concentration, and academic achievement. It was found that using PowerPoint improves students’ understanding of the material, problem solving skills, and information retention.